Investigasi Peleburan dan Pembekuan Phasa Change Material (PCM) Paraffin Wax Sebagai Thermal Energy Storage Pada Pipa - Handoko, R; Suwandi, A; Siregar, Chandra A; Siregar, Ahmad Marabdi (Fakultas Teknik UMSU, 2023)
Phase change materials (PCM) are materials that can change phase from solid to liquid and vice versa from water to solid. PCM is the most efficient material for storing heat energy in the form of latent heat. This study aims to investigate melting and freezing of PCM types of paraffin wax in pipes. The investigation was carried out in 3 experiments with heat source temperatures of 90 0C, 85 0C and 80 0C. To facilitate investigation, paraffin wax is placed in a transparent tube. During the smelting process, observations were made for 600 minutes, and data recording and shooting were carried out every 60 minutes. The result is that the melting of paraffin wax starts from the top of the heat source side. The higher temperature paraffin wax moves upwards and the lower one moves downwards. On freezing, also found the same thing. The flow pattern is affected by the temperature of the paraffin wax itself. In addition, it can also be concluded that the higher the temperature of paraffin wax, the higher its ability to store heat energy.